(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to estimate the deployment time of Containerized application using Novel Microsoft Azure basedDocker Container over Google cloud platform based docker container. Materials and Methods: Sample groups that are considered in the project can be classified into two each has 20 samples, one for Google cloud platform and other for Novel Microsoft Azure based docker container, which are tested using 0.80 for Gpower to determine the sample size and for t-test analysis. 20 applications have been used in each group for estimating deployment time. Results: The Novel Microsoft Azure based Docker container with efficient accuracy of 77%, which by far seems to be better than the Google cloud platform based docker container which gives around 70.00%. As a result, the study group has a statistically negligible difference. The significance is around 0.0477 (p<0.05) and therefore there is a statistical insignificant difference among the study group. Conclusion: The deployment time of Containerized application in the Novel Microsoft Azure based Docker container is better compared to Google cloud platform based docker container.